2001
DOI: 10.1016/s0002-9270(00)02422-9
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative morbidity, mortality, costs, and long-term survival in severely obese patients undergoing orthotopic liver transplantation

Abstract: Despite higher postoperative complications, severely obese patients have an acceptable long-term survival, which is comparable to nonobese patients. The cost of transplantation is higher among severely obese patients. There was no increased incidence of cardiovascular mortality among severely obese patients during the follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 12 publications
2
90
1
4
Order By: Relevance
“…Because LDLT recipients are generally younger and less likely to be obese than cadaveric recipients, the occurrence of wound complications in LDLT recipients may be lower than in historic controls. [16][17][18] The lower rate of obesity in the sirolimus cohort and trend toward lower body mass index (25.5 v 26.1 kg/m 2 ) likely is caused by the greater proportion of LDLT recipients in the sirolimus cohort.…”
Section: Discussionmentioning
confidence: 98%
“…Because LDLT recipients are generally younger and less likely to be obese than cadaveric recipients, the occurrence of wound complications in LDLT recipients may be lower than in historic controls. [16][17][18] The lower rate of obesity in the sirolimus cohort and trend toward lower body mass index (25.5 v 26.1 kg/m 2 ) likely is caused by the greater proportion of LDLT recipients in the sirolimus cohort.…”
Section: Discussionmentioning
confidence: 98%
“…Results of other studies suggest that obese patients have higher post-transplant complications, longer hospital stays and higher hospital costs. [101][102][103][104][105][106] Obesity may also exaggerate the negative impact of risk factors such as donor graft cold ischemia time. 107 Patients with diabetes or coronary artery disease, both commonly associated with obesity, are approximately 40% more likely to die within 5 years of liver transplantation compared to non-diabetics or to patients without coronary artery disease.…”
Section: Malnutrition and Outcome Following Liver Transplantationmentioning
confidence: 99%
“…[11][12][13][14] Single center studies on liver transplantation have shown inconsistent results mainly because of the differences in the definition of obesity, sample size, reporting, and selection bias. [15][16][17][18][19] These studies, however, showed a trend toward higher postoperative complications, length of hospital stay, and hospital costs for obese recipients. 17,19 In many of the above single center studies, patients with BMI Ͼ30 kg/m 2 were grouped together and therefore, the impact of severe or morbid obesity on sold organ transplantation could not be assessed independently.…”
Section: See Article On Page 1678mentioning
confidence: 99%
“…[15][16][17][18][19] These studies, however, showed a trend toward higher postoperative complications, length of hospital stay, and hospital costs for obese recipients. 17,19 In many of the above single center studies, patients with BMI Ͼ30 kg/m 2 were grouped together and therefore, the impact of severe or morbid obesity on sold organ transplantation could not be assessed independently. Moreover, the sample size of these studies was inadequate to assess the independent effect of severe or morbid obesity on liver transplant outcomes.…”
Section: See Article On Page 1678mentioning
confidence: 99%
See 1 more Smart Citation